Synthesis and Biological Evaluation of N'-Arylidene-4-Hydroxybenzohydrazides against α-Glucosidase Enzyme - Danova, Ade; Hermawati, Elvira; Chavasiri, Warinthorn (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2023)
Hydrazides have been reported to have a broad spectrum of bioactivities, such as anticancer, antifungal, antibacterial, and antidiabetic. Thus, our work aimed to synthesize N'-arylidene-4-hydroxybenzohydrazides and investigate their α-glucosidase inhibition. Three compounds (AD-H1-3) were synthesized with a yield of product from 33 to 65% and then characterized using 1H-and 13C-NMR spectroscopy. The in vitro α-glucosidase inhibition demonstrated that AD-H2 possessing two hydroxy groups on arylidene moiety showed the best inhibitory activity against α-glucosidase enzyme with an IC50 value of 14.4 µM compared with acarbose as a positive control with IC50 value of 93.6 µM. Thus, AD-H2 could be a candidate as a lead compound for antidiabetics.